New Hexanuclear Feiii Clusters with the Gem-Diol Hydrated Form of Di(2-Pyridyl)Ketone and Carboxylato Ligands: Crystal Structures and Magnetic Properties - Canon-Mancisidor, W; Canon-Mancisidor, W (Elsevier Ltd, 2019)
The hexanuclear compounds [Fe6O2Cl2{(py)2CO2}2(pyOH)2(pyCOO)2(ButCOO)6] (1) and [Fe6O2{(py)2CO2}2(pyCOO)4(ButCOO)6] (2) were obtained by condensation of the trinuclear μ3-oxo-centered iron(III) pivalate [Fe3O(ButCOO)6(H2O)3]+ in the presence of di(2-pyridyl)ketone [(py)2CO] in MeCN at ambient temperature. Both complexes contain an analogous core which can be described as two {Fe3O}7+ units joined by gem-diolato (py)2CO22− bridges. Variable-temperature magnetic susceptibility measurements in polycrystalline samples of 1 and 2 reveal strong antiferromagnetic couplings between the iron(III) ions leading to S = 0 ground states. © 2019 Elsevier Ltd